(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2024)
Objective: When abnormalities in kidney structure or function are evident for more than three months, it is referred to as chronic kidney disease (CKD), a complicated and progressive chronic disorder that can have devastating health effects. Either reduced glomerular filtration rate or indicators of renal injury could be evident. End-stage renal disease (ESRD) patients are increasingly choosing PD, HD, and kidney transplantation as treatments to extend their lives because of the development of renal replacement therapies, such as kidney transplantation, hemodialysis (HD), peritoneal dialysis (PD), and continuous renal replacement therapy (which is frequently used for acute renal failure). Loss of muscle mass may result from dialysis treatments that increase protein breakdown and decrease protein synthesis. These reactions continue after dialysis. The purpose of this research is to look into the connection between the ghrelin. Materials and Method: In order to determine the blood lipid profile and Ghrelin hormone levels, 90 individuals with Chronic Kidney Disease (CKD) on dialysis were divided into 45 males, 45 females, and 90 healthy subjects. The Ghrelin hormone concentration was compared with the other biochemical parameters, and the relationship between the hormones Ghrelin and Nitric Oxide was also found. Results: Ninety healthy subjects and ninety chronic kidney disease (CKD) patients with dialysis had their blood lipid profiles and Ghrelin hormone and nitric oxide levels measured. The results included a comparison of the hormone’s concentration with other biochemical parameters and the identification of the hormone’s relationship with nitric oxide. Results: When compared to the control group, dialysis patients’ nitric oxide levels significantly decreased (p≤0.05). There were no discernible variations in the levels of serum nitric oxide between the sexes. (p < 0.05).Ghrelin levels in the blood serum of dialysis patients were significantly lower than those in the control group (p≤0.05). Additionally, it was demonstrated that the level of the hormone Ghrelin was significantly lower in females than in males (p≤0.05). Conclusion: When comparing dialysis patients to the control group, we detect a significant drop in the levels of Ghrelin Hormone and Nitric Oxide in patients with chronic kidney disease.It follows that low nitric oxide and ghrelin levels in chronic renal disease patients can cause kidney failure to progress to an advanced degree and eventually require dialysis.